Associations of estimated 24-h urinary sodium excretion with mortality and cardiovascular events in Chinese adults: a prospective cohort study. Issue 3 (6th March 2021) - Liu, Xiaoyun; Bai, Yinxiao; Li, Sidong; O'Donnell, Martin; Mente, Andrew; Yin, Lu; Hu, Bo; Cheng, Xiaoru; Liu, Weida; Bai, Xiulin; Wang, Yang; Sun, Yi; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To investigate the associations of sodium excretion with blood pressure, mortality and cardiovascular diseases in Chinese population. Methods: We studied 39 366 individuals aged 35–70 years from 115 urban and rural communities in 12 centers across mainland China. Trained research staff conducted face-to-face interview to record baseline information of all participants based on questionnaires, and collected their morning fasting urine samples to estimate 24-h sodium excretion (24hUNaE). Multivariable frailty Cox regression accounting for clustering by centre was performed to examine the association between estimated 24hUNaE and the primary composite outcome of death and major cardiovascular events in a Chinese population. Results: Mean 24hUNaE was 5.68 (SD 1.69) g/day. After a median follow-up of 8.8 years, the composite outcome occurred in 3080 (7.8%) participants, of which 1426 (3.5%) died and 2192 (5.4%) suffered from cardiovascular events. 24hUNaE was positively associated with increased SBP and DBP. Using the 24hUNaE level of 4–4.99 g/day as the reference group, a 24hUNaE of either lower (<3 g/day) or higher (≥7 g/day) was associated with an increased risk of the composite outcome with a hazard ratio of 1.22 (95% confidence interval: 1.01–1.49) and 1.15 (95% confidence interval: 1.01–1.30), respectively. A similar trend was observed between 24hUNaE level and risk of death or major cardiovascular events. Conclusion: These findings support a positive association between estimated urinary sodium excretion and blood pressure, and a possible J-shaped pattern of association between sodium excretion and clinical outcomes, with the lowest risk in participants with sodium excretion between 3 and 5 g/day.